Feelings and perceptions of Unified Health System-dependent users cured of COVID-19 - de Souza Franco, Joclécia Kauanne; Medeiros Souza, José Madson; Santos Alves, Rayanne; Martins Simões Candeia, Rozileide; da Silva Santos, Jaylane; Salvino da Silva, Rayane; Medeiros Pontes, Vitória (O Mundo da Saúde, 2022)
Due to the whole context of pandemic and its social impacts, a fragile situation in public health is faced, and may not only cause physical illness, but especially mental suffering, which has a high chance of occurring in the general population and persisting with post-pandemic psychological symptoms. The study aimed to understand feelings and perceptions experienced by dependent UHS users affected by Coronavirus, as well as the sequelae resulting from the process of illness and cure of the virus. This is descriptive, exploratory study type with a qualitative approach. The collection was carried out in the municipality of Guarabira, PB, with 20 dependent UHS users, who were affected by COVID-19, and who had been cured for at least 1 month. Users were invited to participate in the research through social networks. The interviews were guided by the data collection instrument and conducted remotely, using digital audio and video platforms. The age range of the interviewees ranged from 20 to 63 years, and 17 (85%) were females and 3 (15%) were males. Most females had completed higher education and were single. Feelings such as fear, anxiety, anguish, and loneliness, and the presence of sequelae after the cure of COVID-19 were identified. These feelings were clearly exposed in the interviewees’ statements and the most prevalent feeling was fear. The study allowed for the identification of feelings harmful to the mental health of the participants. Through the reports, the presence of important sequelae after the cure of COVID-19 was also identified.